RAGE modulatory effects on cytokines network and histopathological conditions in malarial mice - Chin, Voon Kin; Chuah, Yaw Kuang; Nordin, Norshariza; Ibraheem, Zaid Osamah; Zakaria, Zainul Amiruddin; Hassan, Haniza; Basir, Rusliza (Elsevier BV, 2020)
This study was aimed at investigating the involvement of Receptor for Advanced Glycation End Products (RAGE) during malaria infection and the effects of modulating RAGE on the inflammatory cytokines release and histopathological conditions of affected organs in malarial animal model. Plasmodium berghei (P. berghei) ANKA-infected ICR mice were treated with mRAGE/pAb and rmRAGE/Fc Chimera drugs from day 1 to day 4 post infection. Survival and parasitaemia levels were monitored daily. On day 5 post infection, mice were sacrificed, blood were drawn for cytokines analysis and major organs including kidney, spleen, liver, brain and lungs were extracted for histopathological analysis. RAGE levels were increased systemically during malaria infection. Positive correlation between RAGE plasma concentration and parasitaemia development was observed. Treatment with RAGE related drugs did not improve survival of malaria-infected mice. However, significant reduction on the parasitaemia levels were recorded. On the other hand, inhibition and neutralization of RAGE production during the infection significantly increased the plasma levels of interleukin (IL-4, IL-17A, IL-10 and IL-2) and reduced interferon (IFN)-γ secretion. Histopathological analysis revealed that all treated malarial mice showed a better outcome in histological assessment of affected organs (brain, liver, spleen, lungs and kidney). RAGE is involved in malaria pathogenesis and targeting RAGE could be beneficial in malaria infected host in which RAGE inhibition or neutralization increased the release of anti-inflammatory cytokines (IL-10 and IL-4) and reduce pro-inflammatory cytokine (IFNγ) which may help alleviate tissue injury and improve histopathological conditions of affected organs during the infection.